(3eLehYI CTYGQ dbOGei heMOKjfs - (3eLghds
(3ChdgG (B:s
(3ef dGejI GdYQH ddTfaQj, bhdg(B: (3CbjehG Hfj oCej oUOhQ eWjce aEfj Edi Cgd ShGce dGejod s
(3BNQgG (B:s
(3hYQaJ Gdge oeP aGQbJce acCfj eG YQaoJ GdaQMG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3hGdfSNI ajgG VHW hHgG JbWjYs
(3heYgG HYV CNHGQ hfbhd efgG dGejI GdYQH ddTfaQj , hGHf MLI GdMehj, hUdGM GdOjf GdUaOj, hHgGA GdOjf RgjQ, hGHf GdebQH, hGHf fHGJI, hcTGLe, hCHj GdYJGgjI, hSfGA Gdedc, hUaj GdOjf GdMdj, hCHj JeGe, hGdReNTQj, hZjQges
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs